Injustice : Gods Among Us Year Two Volume 1 - Taylor, Tom, 1978- (DC Comics, 2014)
"The best-selling prequel to the hit videogame picks up right where it left off! Year one is over--now, year two begins. The death of one of their own has divided Earth's protectors as hero turns against hero. As Superman's iron grip on the world tightens, at the edge of the galaxy, anothe grave threat approaches ... INJUSTICE: GODS AMONG US YEAR 2 continues the story from the New York Times best-selling graphic novel with rising star writer Tom Taylor (EARTH 2) and a team of artists including Mike S. Miller, Bruno Redondo and Julien Hugonnard-Bert"--